African American Culinary History and the Genesis of American Cuisine: Foodways and Slavery at Montpelier. (3rd May 2020) - Pavão-Zuckerman, Barnet; Oliver, Scott; Copperstone, Chance; Reeves, Matthew; Harte, Marybeth
ABSTRACT: American Southern foodways emerged in large part within the kitchens of slave plantations, where enslaved Black cooks incorporated African, Native American, and European practices and foods to create distinctly American food traditions. We use animal remains excavated from James Madison's Montpelier to illuminate early American cuisines in the Virginia piedmont. Black foodways at Montpelier were not monolithic. Pork and beef were the dominant meats consumed by all enslaved community members, and all communities supplemented their rations with their own subsistence pursuits to some extent. However, differential access to time, technology, and contact with white enslavers led to disparate circumstances for enslaved communities in terms of their relative reliance on rationed meats versus wild game, particularly fish.